Rediseño de la planta productiva de Carnes Verona que satisfaga la demanda proyectada de chorizos mixtos en el mercado bogotano (2017)
Carnes Verona is a charcuterie business located in Zipaquira that commercializes its products in the Sabana towns of Cundinamarca, has reached a position in the market and a commercial growth. Currently, this business underutilizes its resources after an investment that allowed it to grow its productive capacity. Hence, this business looks for new markets to reach a demand that allows them to use all its productive capacity. Bogota has been always a potential market, although it has never been reached because of restrictions such as distance and lack of knowledge about the customers. Knowing that Bogota has a bigger population that the current market of Carnes Verona (which is 6,5 % of Bogota`s population), a question arises do Carnes Verona have the necessary resources to supply its demand after a period of time, taking into account the last year’s growth and its acceptance in each town where they`ve entered? Being such a big market, a selection of economic sectors -including places ready to consume mixed chorizo- is needed. A redesign of the productive plant was made, taking into account the projected demand of mixed chorizo after the market dimensioning of selected sectors in Bogota and the current market of Carnes Verona. This process productive plant to grow its capacity, all this was done through changes in paths and the location of machines, so operators can go through shorter distances and have less crossing through the process. This change achieves a reduction in the total time of production and more lots produced daily.